In a jar - Marcero, Deborah (New York : G. P. Putnam's Sons, 2020)
When Llewellyn, a little rabbit who collects ordinary things in jars, meets a young girl named Evelyn, he joins with her to capture the extraordinary.
School Library Journal starred, December 2019
Booklist starred, November 2019
Publishers Weekly, September 2019
Kirkus Starred, October 2019
Library Media Connection, November 2019
3.5
Keywords: Collectors and collecting -- Juvenile fiction; Friendship -- Juvenile fiction; Rabbits -- Juvenile fiction; Collectors and collecting -- Fiction; Friendship -- Fiction; Rabbits -- Fiction; Animal fiction